Vulnerabilidad social y política al VIH-sida en Bogotá (2021)
This study aimed to establish the processes and social factors that determine vulnerability to HIV/AIDS and to examine the role of public policy to increase said social vulnerability in Bogotá. The methodological itinerary had as its starting point a qualitative approach that articulated four traditions of study (critical public health, critical anthropology of health, sociology of medical practice and evaluation of public policies) and various strategies: documentary research, analysis of district policy, and semi-structured interviews conducted with public health institutions and community-based organizations. The results revealed the political inability to guarantee the right to life and health of people living with HIV/AIDS, to eliminate stigma, discrimination and gender-based violence. Therefore, some recommendations are provided to reorient public policy in this matter.